Berkenalan dengan aliran-aliran dan tokoh-tokoh psikologi - Sarlito Wirawan Sarwono (Bulan Bintang, 1978)
Bhr/C.1-8/ oen,C.9/ oen, C.10-11/ir,c.12, sgh c13/ir,c.14/oen, c.15/oen, c.16-17/stoc6, c.1-17